Exposure‐Response Characterization of Tofacitinib Efficacy in Moderate to Severe Ulcerative Colitis: Results From Phase II and Phase III Induction and Maintenance Studies. Issue 1 (27th April 2022) - Mukherjee, Arnab; Tsuchiwata, Shinichi; Nicholas, Timothy; Cook, Jack A.; Modesto, Irene; Su, Chinyu; D'Haens, Geert R.; Sandborn, William J.
Abstract : Tofacitinib is an oral small molecule JAK inhibitor for the treatment of ulcerative colitis. Relationships between plasma tofacitinib concentration and efficacy were characterized using exposure‐response (E‐R) models, with demographic and disease covariates evaluated as potential predictors of efficacy. Data were from phase II and III (OCTAVE Induction 1 and 2) induction studies, and a phase III maintenance study (OCTAVE Sustain). Induction studies included 1, 355 patients (tofacitinib 0.5, 3, 10, or 15 mg b.i.d. or placebo). The maintenance study included 592 patients (tofacitinib 5 or 10 mg b.i.d. or placebo). E‐R models, including induction patients predicted placebo‐adjusted remission rates of 6.4% and 12.7% at week 8 for tofacitinib 5 and 10 mg b.i.d., respectively; corresponding rates in patients without prior tumor necrosis factor inhibitor (TNFi) failure were 12.8% and 20.4%. Estimates to achieve/maintain remission at week 52 of maintenance were 29% and 18% (tofacitinib 5 mg b.i.d.), and 41% and 26% (tofacitinib 10 mg b.i.d.), for patients in remission or not following induction, respectively. During maintenance, patients with prior TNFi failure had lower probability of remission on 5 mg b.i.d. (24.9%) than 10 mg b.i.d. (35.0%). Results indicated tofacitinib 10 mg b.i.d. was an appropriate induction dose but suggested efficacy with 5 mg b.i.d. in patients without prior TNFi failure. Tofacitinib 5 mg b.i.d. was efficacious for maintenance, although patients with prior TNFi failure might see additional benefit on 10 mg b.i.d. Per product labeling, recommended tofacitinib induction dose is 10 mg b.i.d., then maintenance at 5 mg b.i.d. For patients who lose response during maintenance, 10 mg b.i.d. may be considered, limited to the shortest duration. Clinicaltrials.gov: NCT00787202; NCT01465763; NCT01458951; and NCT01458574.